Answer:
Algebraic expression = (x-43)^3
Explanation:
Given , the verbal expression is the cube of the difference of a number and 43.
Let x be the number
Now, according to question
Difference means subtraction in which a number is subtracted from the other number
Difference of a number and 43
It means 43 is subtracted from x
Now , the algebraic expression =x-43
Cube of the difference of a number x and 43 =(x-43)(x-43)(x-43)
Cube of a number means multiply a number three times with self .
Therefore, Cube of the difference of a number x and 43=
![(x-43)* (x-43)*(x-43)](https://img.qammunity.org/2020/formulas/mathematics/high-school/rdj8crq6enj5m3lrsvagxsrbk1x1vg2sb1.png)
Cube of the difference of a number x and 43=(x-43)^3
Because in multiply when base same then power of the number added.
Hence,the algebraic expression =(x-43)^3.
I